Rumah Baca dan Youth Center di Solo Baru - Purwanto, Pendi, M.S. Priyono. N. ST, MT (2016)
To foster interest in reading is lower then the necessary holding of a new facility that can stimulate interest in reading. At the present time the manufacturer or producer reference library of books increased demand from the public, and therefore required a media campaign and distribution. Media distribution in question is the bookstore as commercial space and the library are more oriented to service or function library catalog. Some libraries also serves as a gathering place for the community or several people. Along with the needed information through books, the number of books into the market is increasing. This makes selective public to choose the goods on offer. Meanwhile other needs as a form of social pattern changes in the information age began to emerge as actualization or interaction between the library community, therefore, should be considered an alternative media to accommodate such activities. Adolescence is synonymous with the social environment interact, making them required to adjust themselves effectively. When the activities undertaken in schools is not adequate to meet the energy demands of the turmoil, the teenagers often vent excess energy in the direction that is not positive, such as fights, drugs and others. To prevent that, the necessary container for menampug activities of the youth to vent the energy and creativity that tepat.Maka place to read mengabungkan between home and expected to facilitate a youth center for education and talent of the adolescent. Keywords: Interest Read, New Facility, Youth.